Maulid Diba’ sebagai Peningkat Religiusitas Mahasantri Komplek H Pondok Pesantren Krapyak Yayasan Ali Maksum Yogyakarta - Ilzam Hubby Dzikrillah Alfani (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Salawat Maulid Diba' is very popular among the community and Islamic boarding schools of the Nahdlatul Ulama family. The culture of reciting the Maulid Diba salawat has been passed down from generation to generation. Mawlid Diba's routine readings are able to influence the body and soul of the readers, including material and immaterial. This paper discusses Mawlid Diba' as an increase in the religiosity of Mahasantri Complex H Krapyak Ali Maksum Islamic Boarding School. Research Using a qualitative approach. The method used is phenomenology. This type of research is field research. The results of the study show that reading Mawlid Diba' activities can increase the religiosity of Mahasantri Complex H. In general, it can get used to positive activities, improve discipline, especially in managing time. Religiously, it can increase faith in Allah and the Messenger, increase love for Allah and the Messenger, emulate the example of the Apostle, strengthen friendship, make people happy, the mind is calm, and the heart is comfortable.